The Impact of Islamic Economics Principles on the Tax Compliance Payment Entertainment Policy - Bambang Tri Bawono; Abdul Kadir Jaelani; Rian Saputra; Bobur Baxtishodovich Sobirov; Gaini Mukhanova (JURIS (Jurnal Ilmiah Syariah), 2024)
Surakarta City Government has established various entertainment tax rate policies; however, entertainment taxpayers must still comply with these policies. This research examines and analyzes the impact of Islamic economics principles on the tax compliance payment entertainment policy. This research is normative research equipped with interviews. This research uses descriptive secondary data. The research results show that, first, the level of tax compliance in paying massage parlor and SPA entertainment taxes in Surakarta City differs from Islamic economics principles. At the same time, the causal factor is the minimal participation of taxpayers in formulating entertainment tax rate policies. Second, the Surkarta City government has a role in increasing tax compliance in massage parlors. SPA Entertainment is maximizing the imposition of sanctions, supervision, outreach, and providing applications that make tax services easier.